2018
DOI: 10.1108/ijwhm-04-2018-0055
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers and facilitators to workplace exercise participation

Abstract: Purpose Workplace exercise programmes have been shown to increase employee participation in physical activities and improve health and fitness in the short-term. However, the limited breadth of employee engagement across organisations combined with declining exercise adherence within individual studies indicates a need for better-informed programmes. The purpose of this paper is to investigate relationships between employee moderate-vigorous physical activity (exercise) participation and their perceived barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 45 publications
3
40
0
Order By: Relevance
“…While the reasons for non-participation were not investigated in this study, it is possible that paramedics with a stronger affinity towards exercise chose to participate (i.e. selection bias) [27] and/ or those with previous musculoskeletal injuries or medical conditions chose not to participate. Had a greater proportion of the overall paramedic population participated (including older paramedics), mean fitness outcomes may have been poorer than those observed in the current sample.…”
Section: Discussionmentioning
confidence: 99%
“…While the reasons for non-participation were not investigated in this study, it is possible that paramedics with a stronger affinity towards exercise chose to participate (i.e. selection bias) [27] and/ or those with previous musculoskeletal injuries or medical conditions chose not to participate. Had a greater proportion of the overall paramedic population participated (including older paramedics), mean fitness outcomes may have been poorer than those observed in the current sample.…”
Section: Discussionmentioning
confidence: 99%
“…For many workers, physical activity is their primary non-work-related interest. For example, in a recent study, most employees reported meeting (43.7%) or exceeding (42.9%) physical activity guidelines over the previous week (Hunter, Gordon, Bird, & Benson, 2018). However, we still have a limited understanding about if and how passion for non-work related activities, such as physical activity, may spillover into the workplace and influence life satisfaction, performance, and innovativeness.…”
Section: The Dualistic Model Of Passionmentioning
confidence: 99%
“…For managers attempting to enhance performance and innovation among employees, the present research suggests that one way to accomplish this is to look beyond the formal work environment and instead toward extra-curricular physical activity. Many organizations already have such programs in place, through free or discounted gym memberships, or by integrating fitness tracking technologies (such as the Fitbit) into employee wellness programs (Hunter et al, 2018). However, there is an important caveat.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Yet little is known about which factors influence participation in workplace exercise behavior [ 15 , 32 , 33 ]. There are many barriers to physical exercise at the office, such as lack of time to perform physical activities [ 34 ], work burden and performance concerns [ 35 ], workplace policies and norms [ 36 ]. For instance, performing physical exercises in the workplace may be heavily influenced by colleagues’ and superiors’ behavior and attitude [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are many barriers to physical exercise at the office, such as lack of time to perform physical activities [ 34 ], work burden and performance concerns [ 35 ], workplace policies and norms [ 36 ]. For instance, performing physical exercises in the workplace may be heavily influenced by colleagues’ and superiors’ behavior and attitude [ 34 ]. There are also several limitations in the office environment, such as lack of public space and public facilities [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%